Recent climate changes of thermohaline structure in the North-West Pacific - Vladimir I. Byshev; Alexander L. Figurkin; Ivan M. Anisimov (Известия ТИНРО, 2016)
Variability of temperature and salinity in the 0-1000-m layer of the North-West Pacific is analyzed on the data of shipboard oceanographic observations obtained in 1950-2014. Significant decadal changes of these parameters are revealed at the depth of 300-600 m that exceeds the depth of seasonal fluctuations, with the highest rate in the Subarctic frontal zone. The heat content was the highest in the 1960-1974, then decreased in the 1975-1999, increased again in the 2000-2014, and the next phase of thermal «discharge» may begin supposedly in 5-6 years. Mechanisms of such climate changes are discussed. Similar changes are observed in different regions of the World Ocean that means that it is a global-scale phenomenon. These climate changes of water temperature in the subsurface layer of the ocean and air temperature over the continent have opposite directions that denotes the auto-oscillation in the open non-linear system «ocean-atmosphere-continent» as their main mechanism. The previous period of the water thermal discharge was conditioned by active winter center of low atmospheric pressure - Aleutian Low. It was accompanied by strengthening of the East-Kamchatka Current and Oyashio Current and high abundance of japanese sardine. The modern period of warming from the beginning of the 21st century is distinguished by negative values of PDO index, observed since 1998. However, PDO is positive again since January 2014, though stability of this change is not clear yet. On the other hand, winter SST in the spawning grounds of japanese sardine, both in the Japan Sea and North-West Pacific, gradually decreased after the maximum in the 1998-2000 and reached negative anomalies in the areas at Japan in 2011-2015 that was favorable for its reproduction. The sardine biomass was gradually increased, too, in particularly in the 2010-2012, and its migration to the Russian EEZ became more active, up to 0.7 million tons in the South-Kuril area in 2015.